Avaliação do desempenho econômico-financeiro nas operações do BNDES: uma análise ao nível da firma das empresas de capital aberto entre 2002 e 2018 - Cappello, Felipe Adolfo (2019)
This work deals with the roles of the Brazilian National Bank for Social and Economic Development (BNDES) and the economic and financial performance of publicly traded companies that sought financial resources from this federal public company. Considering previous work to accomplish this task, a multivariate analysis was performed aiming to observe the relationship between BNDES fundraising and the Capital Structure and its relationship with the economic-financial performance between 2002 and 2018, considering liquidity indicators, profitability, market and value generation as components of the roles: Counter Cyclic, Industrial Developmental, Conjunctural and Political Vision and Rent Seeking; indicated by the literature on development finance agencies. After analyzing the results, it was found that BNDES borrowers are reasonable to state the absence of superior financial economic performance as a consequence of subsidized capital, when compared to companies that did not take this same resource and that borrowers tend to a continuous increase in the risk of its operations and together with the decrease in return on investment (ROIC), which makes it reasonable to state the absence of operations capable of generating competitive advantage